ARBITRASE SEBAGAI LEMBAGA PENYELESAIAN SENGKETA MENURUT UNDANG-UNDANG NO. 30 TAHUN 1999 - Yunari, Afrik (IAIN Tulungagung, 2015)
In case of dispute settlement via the outside court, then offered severalalternative dispute resolutions which give the ease with which theprocess is fast, cheap and resolved as well as possible, one of whichuses the process of arbitration. Arbitration is the most interestingoption in order to resolve the dispute in accordance with their wishesand needs. So, resolving disputes through arbitration is regulatedspecifically in Act No. 30/1999 regarding arbitration and alternativedispute resolution. In many civil agreement cases, arbitrate clausewidely used as dispute for resolution options. Legal opinion givenarbitration institutions are independent, final, and binding. Becauseof the opinions given will be the part that is inseparable from theagreement staples. Each of the opposite opinion against the opinionof the law means a violation of the Covenant (breach actions ofcontract-tort). Therefore resistance cannot be made in the form ofany remedy. In this paper discusses about the arbitration as disputeresolution institutions according to act No. 30/1999 which include:understanding of arbitration, the arbitral seat as non litigation, prosand cons of arbitration dispute, the kind that become arbitrationauthority, implementation of the ruling of the arbitration and thestrengths of arbitration decision.Kata kunci: Arbitrase, Lembaga Penyelesaian Sengketa, Undang-Undang No. 30 Tahun 1999